Clustering of KOR PET images separates people with AUD into distinct responses to naltrexone - Hoye, Jocelyn; Key, Jose; de Laat, Bart; Cosgrove, Kelly P.; Krishnan-Sarin, Suchitra; Papademetris, Xenophon; Morris, Evan D. (Brain imaging and behavior, 2023)
Striatal kappa opioid receptor (KOR) availability in 48 subjects with Alcohol Use Disorder (AUD) was previously found to be associated with degree of drinking following a week of naltrexone treatment (de Laat et al. Biological Psychiatry , 86 (11), 864-871, 2019 ). The purpose of the current study was to determine if spectral clustering applied to previously acquired KOR images (with [11C]LY2795050 PET) could identify meaningful groupings of different responses to naltrexone and to assess the robustness of the finding. Spectral clustering was applied to 6 features (regional volume of distribution values, V T ) per AUD subject to produce 3 classes of subjects with different mean responses to naltrexone. Response to naltrexone was quantified as the difference in drinks consumed in an established lab-based alcohol drinking paradigm (Krishnan-Sarin et al. Biological Psychiatry , 62 (6), 694-697, 2007 ) prior to, and after a week of naltrexone treatment. Clustering was applied exclusively to features of the image data with no a priori knowledge of the subjects’ responses. Separation of classes was tested using a 1-way analysis of variance (ANOVA) with drink reduction as the outcome of interest. To assess robustness of the result, the size of the training set was varied by using successively reduced subsets of the data. Clustering resulted in significantly different groupings of drink reduction. The finding was robust to initialization of the spectral clustering procedure and was replicable for different random subsets of training subjects. Finding: Spectral clustering of kappa PET images separates AUD subjects into behaviorally distinct groups expressing distinct responses to naltrexone.